Study of Structural Properties of BiOI on ZnO Thin Films and ZnO Nanorods - C. D. Gutiérrez-Lazos; A. Fundora-Cruz; F. Solís-Pomar; E. Pérez-Tijerina (Advances in Materials Science and Engineering)
We report the study of ZnO nanorods (ZnO-NR) decorated with BiOI nanoplatelets by the simple precipitation of BiOI in aqueous solution containing ZnO-NR powders. Likewise, as a reference for the decoration of ZnO-NR, BiOI thin films were prepared by the SILAR technique on RF magnetron-sputtered ZnO thin films. The scanning electron microscopy analysis showed that BiOI grew on the ZnO-NR surfaces in nanoplatelet shape with an order of magnitude smaller in size, with respect to the platelets observed in BiOI thin films. Analysis by X-ray diffraction exhibited the hexagonal P63mc phase of ZnO and the tetragonal P4nmm crystal phase of BiOI. On the other hand, BiOI thin films are nonuniform and strongly adherent and, besides they exhibited the P4nmm tetragonal crystal structure of BiOI, they have highly preferential orientation along (001) direction (9.66°). Optical characterization of ZnO-NR/BiOI by absorbance showed a widened peak slightly shifted to infrared compared with the ZnO-NR absorbance peak, suggesting the increase of the absorption wavelength ranges from the ultraviolet to visible for ZnO-NR. Similarly, the results of the optical characterization by absorbance, for BiOI thin films, indicated the bandgap energy of the samples was between 1.78 eV and 1.88 eV, values previously reported for BiOI.